Amazonian Communities: Shaping the Ethics of Cosmocentrism - Varese, Stefano (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
During millennia Amazonia has shaped herself as an integrated cosmos of tangible and intangible beings interweaved as a totality of relatives. This indigenous non-anthropocentric civilizational construction can be better defined by the neologism cosmocentric rather than contemporary ecological terms such as biocentric or geocentric, which emphasize exclusively the materialistic component of the whole system. Colonial and capitalist occupation of Amazonia portrayed and actively reconfigured a manageable “social reconstruction” of Peru’s Amazon Rainforest –La Selva, imposing a new ontology devoid of any ethical concerns. This article will explore the ethnic and political journey of Indigenous Amazonian Communities since the early 1960s to restore a pre-modern and post-modern environmental, cultural, social and ethical conception and practice of Amazonia.